2015
DOI: 10.1136/medhum-2015-010778
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of music therapy for older people among healthcare professionals

Abstract: Purpose of study: To investigate the perceptions of healthcare providers on music therapy and their recommendations on wider adoption in a hospital setting. Design and methods:A qualitative exploratory study employing short semi structured interview using thematic analysis method of data analysis.Intervention: A qualitative exploratory study, employing short semi structured interviews was conducted in March 2015 in an urban teaching hospital to explore healthcare providers attitudes towards and recommendations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
(16 reference statements)
2
7
0
Order By: Relevance
“…This was further confirmed by those students who have elected to undertake their 2nd year research project in arts and health, with publications on aesthetics and stroke,40 the pathography of Igor Stravinsky,41 perception of music therapy for older people among healthcare workers,42 and the study of arts, leisure and culture pursuits of medical students presented here.…”
Section: Arts Culture and Leisure Pursuits Of Medical Studentssupporting
confidence: 69%
“…This was further confirmed by those students who have elected to undertake their 2nd year research project in arts and health, with publications on aesthetics and stroke,40 the pathography of Igor Stravinsky,41 perception of music therapy for older people among healthcare workers,42 and the study of arts, leisure and culture pursuits of medical students presented here.…”
Section: Arts Culture and Leisure Pursuits Of Medical Studentssupporting
confidence: 69%
“…While the impact of PML on ALF personnel was not objectively evaluated, participating MTs endorsed feeling an ease in their work-flow and improved satisfaction with their work, which is similar to other reports. 35 In this ALF, incentives or mandates handed down by facility leadership were not utilized to encourage adoption.…”
Section: Discussionmentioning
confidence: 99%
“…12 Exposure to the arts also has a comforting effect that can offset stress associated with working in a health care environment, facilitate improved staff and patient interaction and rapport building, and create an encouraging hospital experience. 13 Surgeons listening to music in the operating room can reduce their heart rate, blood pressure, and muscle effort while increasing their surgical accuracy and speed at performing tasks. 14 Pa-tients also benefit when hearing music before and during surgery.…”
Section: Increasing Public Health Awareness Of and Capacity For Arts-...mentioning
confidence: 99%
“…However, research has shown that patients have less stress and anxiety, have reduced need for analgesia, and are ready for discharge earlier when the health care environment provides them greater opportunity to view natural and urban scenery . Exposure to the arts also has a comforting effect that can offset stress associated with working in a health care environment, facilitate improved staff and patient interaction and rapport building, and create an encouraging hospital experience . Surgeons listening to music in the operating room can reduce their heart rate, blood pressure, and muscle effort while increasing their surgical accuracy and speed at performing tasks .…”
mentioning
confidence: 99%